Rancang Bangun Trainer Modul Praktikum Programmable Logic Controller Berbasis Outseal PLC Mega V.3 Standar PP - Gea, Susi Susanti; Rahardjo, Pratolo; Nugraha, I Putu Elba Duta (Majalah Ilmiah Teknologi Elektro; Vol 22 No 2 (2023): (Juli - Desember) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2023.v22i02.P20, 2024)
The aim of this research is to design and build a learning trainer using the Outseal Mega V.3 Standard PP PLC board to support the practical in the Programmable Logic Controller + Lab course. The method used in this research is divided into three stages, such as including system design, hardware design, and software design. Testing the practical module of Programmable Logic Controller + Lab consists of three experiments, such as basic operation of Outseal PLC, logic gates, and bell quiz. Based on the result, it can be concluded that the 3 test experiments can be declared successful because the standard Outseal Mega V.3 PLC can be controlled to receive, send, and store data.